2019
DOI: 10.1002/cam4.2425
|View full text |Cite
|
Sign up to set email alerts
|

A randomized phase II trial of nab‐paclitaxel and gemcitabine with tarextumab or placebo in patients with untreated metastatic pancreatic cancer

Abstract: Purpose Notch signaling dysregulation is implicated in the development of pancreatic adenocarcinoma (PDAC). Tarextumab is a fully human IgG2 antibody that inhibits Notch2/3 receptors. Patients and Methods Aphase 2, randomized, placebo‐controlled, multicenter trial evaluated the activity of tarextumab in combination with nab‐paclitaxel and gemcitabine in patients with metastatic PDAC. Patients were stratified based on ECOG performance score and Ca 19‐9 level and randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 26 publications
0
57
0
Order By: Relevance
“…The activity of RIN1 has yet to be assessed, in regard to therapeutic efficacy and intestinal toxicity (31), and comparative evaluation with CB-103 warrants future consideration. One of the major dose-limiting toxicities and hurdles to the therapeutic application of the pan-Notch inhibitor has been intestinal toxicity (22,23). Genetic studies in mice show that Notch acts as a stem and progenitor cell gate keeper and is important for secretory versus absorptive cell fate differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of RIN1 has yet to be assessed, in regard to therapeutic efficacy and intestinal toxicity (31), and comparative evaluation with CB-103 warrants future consideration. One of the major dose-limiting toxicities and hurdles to the therapeutic application of the pan-Notch inhibitor has been intestinal toxicity (22,23). Genetic studies in mice show that Notch acts as a stem and progenitor cell gate keeper and is important for secretory versus absorptive cell fate differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…However, GSIs also block the processing of more than 90 other substrates, which may complicate the interpretation of results produced by GSIs (16). Although both MAbs and GSIs have shown beneficial effects in preclinical Notch-driven tumor models and clinical studies (12,(17)(18)(19)(20)(21), none of these Notch inhibitors have been clinically approved, largely due to on-target dose-limiting toxicities of the intestinal epithelium (22,23). Treatment of patients with GSIs is frequently associated with diarrhea, vomiting, and nausea, which may be severe (24,25).…”
Section: Significancementioning
confidence: 99%
“…In the Phase Ib ALPINE trial, which enrolled 35 patients, tarextumab was generally well-tolerated in patients and demonstrated an encouraging correlation between antitumour activity and Notch 3 activity [ 197 ]. The Phase II portion of this trial, which recruited 177 patients, failed to reach the study endpoint of OS or the secondary endpoints of PFS, ORR and Notch biomarker activity; in fact, tarextumab treated patients had significantly worse outcomes than those on the placebo treatment arm [ 198 ]. Encouraging reports of the Phase Ib PINNACLE trial indicated a dose-efficacy association with a survival benefit in a subgroup of patients (15 of 27 patients enroled) treated with a higher dose of tarextumab, in addition to a manageable safety profile [ 199 ].…”
Section: Inhibiting the Notch Pathway With Molecular-targeted Thermentioning
confidence: 99%
“…Ipafricept is a recombinant fusion protein with the extracellular domain of FZD8 and has been evaluated in combination with chemotherapy in a phase I study for advanced solid tumors [ 140 ]. Tarextumab (OMP-59R5) is an anti-NOTCH2/3 mAb and has been evaluated in phase I/II studies for solid tumors, including pancreatic cancer [ 141 , 142 ] γ-secretase is essential for NOTCH activation, and thus many inhibitors, including MK0752 [ 143 ], BMS-906024 [ 144 ], LY3039478 [ 145 ], RO4929097 [ 146 ], and LY900009 [ 147 ], have been evaluated in combination with/without chemotherapy in phase I studies for advanced or metastatic cancer.…”
Section: Treatments For Cancer Metastasismentioning
confidence: 99%